Zinc-finger protein 545 is a novel tumour suppressor that acts by inhibiting ribosomal RNA transcription in gastric cancer. Issue 6 (12th May 2012) - Wang, Shiyan; Cheng, Yingduan; Du, Wan; Lu, Leina; Zhou, Liang; Wang, Huating; Kang, Wei; Li, Xiaoxing; Tao, Qian; Sung, Joseph J Y; Yu, Jun
Abstract : Objective: Zinc-finger protein 545 (ZNF545) is a member of the family of Krüppel-associated box-containing zinc-finger proteins. The aim of this study was to clarify its biological function as a tumour suppressor in gastric cancer. Design: The biological function of ZNF545 was determined by cell growth and apoptosis assays. The ZNF545 target signal pathway was identified by promoter luciferase assay, northern blot, run-on transcription assay, chromatin immunoprecipitation and coimmunoprecipitation assays. The clinical application of ZNF545 was assessed in primary gastric cancers. Results: ZNF545 was silenced or reduced in 16 out of 18 gastric cancer cell lines by promoter hypermethylation. Restoration of ZNF545 expression in gastric cancer cell lines suppressed cell proliferation and induced apoptosis. These effects of ZNF545 were attributed to inhibition of ribosomal RNA (rRNA) transcription. Inhibition of rRNA transcription by ZNF545 was further revealed to be associated with direct ribosomal DNA (rDNA) promoter binding, recruitment of the corepressor, heterochromatin protein 1β, and reduction of trimethylated histone H3 at the Lys4 residue at the rDNA locus. ZNF545 methylation was detected in 51.9% (41/79) of gastric cancer tissues, 27.0% (20/74) of adjacent non-tumour gastric tissues (p=0.001), but none of 20 normal controls. Multivariate analysis revealed that patients with ZNF545 methylation had a significant decrease in overall survival. Kaplan–Meier survival curves showed that ZNF545 methylation was significantly associated with shortened survival in patients with stage I–II gastric cancer. Conclusions: ZNF545 acts as a functional tumour suppressor in gastric cancer by inhibiting rRNA transcription. Its methylation at early stages of gastric carcinogenesis is an independent prognostic factor.